Gas diffusion layer, membrane electrode assembly, and fuel cell

By forming a microporous layer on the carbon sheet and optimizing the dispersion and bonding materials of carbon fibers, the problem of difficulty in taking into account the conductivity and gas diffusion properties of the gas in solid polymer fuel cells is solved, and the power generation performance of the fuel cell is improved And achieved stable production.

CN112740446BActive Publication Date: 2025-01-03TORAY INDUSTRIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980062125.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-06-28
Publication Date
2025-01-03
Estimated Expiration
2039-06-28

AI Technical Summary

Technical Problem

The gas diffusion layer in the existing solid polymer fuel cell is difficult to take into account both high conductivity and high gas diffusion, which leads to a limit on the power generation performance and makes it difficult to stabilize the production of a gas diffusion layer with sufficient gas diffusion and conductivity.

Method used

By forming a microporous layer on the carbon sheet, the distribution of pores and weight per unit area are controlled, the dispersion of carbon fibers and the use of bonding materials are optimized, and combined with water repellent processing and heat treatment, it has excellent gas diffusion and electrical conductivity. gas diffusion layer.

Benefits of technology

It is achieved to improve both oxygen permeability and electrical conductivity in the fuel cell, thereby improving power generation performance and stably producing a gas diffusion layer with high gas diffusion and electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112740446B_ABST
    Figure CN112740446B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a gas diffusion layer that improves the power generation performance of a fuel cell. The gas diffusion layer comprises a carbon sheet and a microporous layer on at least one side of the carbon sheet, and when a region of the gas diffusion layer having a width of 10 mm and a depth of 3 mm selected arbitrarily is compressed at a pressure of 0.5 MPa in a direction perpendicular to the surface from one side of the gas diffusion layer, the "in-plane oxygen permeability coefficient" of oxygen permeating from the inside of the gas diffusion layer in the in-plane direction is set as A, the "resistance" when the gas diffusion layer is compressed at 2 MPa in a direction perpendicular to the surface is set as B, and the number obtained by subtracting 60 and multiplying B from A and adding 310 is set as the "compatibility index of the in-plane oxygen permeability coefficient and the resistance" C, and when C satisfies the relationship of being greater than 0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas diffusion layer including a carbon sheet and a microporous layer suitable for use in a fuel cell, particularly a solid polymer fuel cell, a membrane electrode assembly including the gas diffusion layer, and a fuel cell including the gas diffusion layer. Background Art

[0002] A solid polymer fuel cell is generally composed of a diaphragm, a gas diffusion layer, a catalyst layer, an electrolyte membrane, a catalyst layer, a gas diffusion layer and a diaphragm stacked in sequence, wherein a fuel gas containing hydrogen is supplied to the anode and an oxidizing gas containing oxygen is supplied to the cathode, and an electromotive force is obtained through an electrochemical reaction between the two electrodes. The gas diffusion layer is required to have the following properties: high gas diffusivity for diffusing the gas supplied from the diaphragm to the catalyst layer, high drainage for discharging water generated by the electrochemical reaction to the diaphragm, and high conductivity for conducting the generated current. Therefore, a gas diffusion layer having a carbon sheet formed of carbon fiber or the like as a substrate and a microporous layer formed on its surface is widely used.

[0003] However, as a subject of such a gas diffusion layer, the trade-off between electrical conductivity and gas diffusion can be cited. A representative factor affecting electrical conductivity is the conductive path formed by the contact between conductive materials such as carbon fibers contained in the gas diffusion layer. In addition, a representative factor affecting gas diffusion is the porosity inside the gas diffusion layer, that is, the amount of gas diffusion path. When a gas diffusion layer that increases the conductive path and reduces the material resistance inside the carbon sheet is made using, for example, a high-density carbon sheet in order to improve electrical conductivity, the gas permeation path inside the carbon sheet is reduced due to the high density of the carbon sheet, and the gas diffusion property deteriorates. On the contrary, when the density inside the carbon sheet is reduced to increase the gas permeation path in order to improve gas diffusion, the conductive path inside the carbon sheet increases and the electrical conductivity deteriorates. In this way, it is difficult to take into account both high electrical conductivity and high gas diffusion. For a gas diffusion layer that is committed to developing one of the properties, the other property has to be sacrificed. Therefore, even if the power generation performance of a fuel cell containing a gas diffusion layer is to be improved, the degree of performance improvement is limited.

[0004] For example, in order to improve the gas diffusion and drainage properties of the aforementioned gas diffusion layer, the following methods have been proposed: in the process of applying a coating liquid as a precursor of a microporous layer to a carbon sheet, by adding water repellency to the conveying roller of the substrate, the aforementioned coating liquid is inhibited from penetrating in the direction perpendicular to the carbon sheet surface, and the gas permeation path inside the substrate is increased (see Patent Document 1); in a gas diffusion layer containing two types of carbon fibers of different sizes, by changing the existence ratio of one of the carbon fibers in a certain direction in the thickness direction, the pore diameter in the thickness direction is changed, and the gas diffusion in the thickness direction is improved (see Patent Document 2). In addition, for the purpose of taking both gas diffusibility and conductivity into consideration, the following method has been proposed: in a precursor sheet of a gas diffusion layer, by improving the dispersibility and interweaving of short carbon fibers, a method of providing a gas diffusion layer having high sheet strength, low manufacturing cost, and excellent gas diffusibility and conductivity is provided (see Patent Document 3).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-50073

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-14275

[0009] Patent Document 3: Japanese Patent Application Publication No. 2015-118944 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, in the invention described in Patent Document 1, the microporous layer precursor is inhibited from penetrating into the carbon sheet, resulting in the possibility that a sufficient microporous layer is not formed inside the gas diffusion layer, the conductive path of the aforementioned gas diffusion layer increases, and the conductivity decreases. In addition, the inventions described in Patent Documents 2 and 3 are gas diffusion layers that do not include a microporous layer, and therefore cannot achieve the same conductivity as a gas diffusion layer that includes a microporous layer. In a gas diffusion layer having a microporous layer, it is important to form a microporous layer at a certain position inside the gas diffusion layer, and therefore the composition and weight per unit area of ​​the microporous layer precursor coating solution must be appropriately controlled according to the structure of the precursor sheet.

[0012] Therefore, in view of the above-mentioned prior art background, an object of the present invention is to provide a gas diffusion layer in which both gas diffusivity and electrical conductivity are improved, thereby improving the power generation performance of a fuel cell including the gas diffusion layer.

[0013] Another object of the present invention is to stably produce a gas diffusion layer having sufficient gas diffusivity and electrical conductivity, which is difficult to produce by conventional methods.

[0014] Furthermore, another object of the present invention is to provide a fuel cell including the above-mentioned gas diffusion layer.

[0015] Means for solving problems

[0016] In order to solve the above-mentioned problems, the inventors of the present application have conducted intensive studies and adopted the following means.

[0017] (1) A gas diffusion layer comprising a carbon sheet and a microporous layer on at least one side of the carbon sheet,

[0018] When a region of the gas diffusion layer having a width of 10 mm and a depth of 3 mm selected arbitrarily from one side of the gas diffusion layer is compressed at a pressure of 0.5 MPa in a direction perpendicular to the surface, the "in-plane oxygen permeability coefficient" of oxygen permeating from the inside of the gas diffusion layer in the in-plane direction is defined as A.

[0019] The "resistance" when the gas diffusion layer is compressed in a direction perpendicular to the surface at 2 MPa is defined as B.

[0020] When the number obtained by subtracting 60 and multiplying B from A and adding 310 is used as the "compatibility index of in-plane oxygen permeability coefficient and electrical resistance",

[0021] The relationship that C is greater than 0 is satisfied.

[0022] (2) a gas diffusion layer comprising a carbon sheet and a microporous layer on at least one side of the carbon sheet,

[0023] The aforementioned carbon sheet has:

[0024] a region including carbon fibers and occupied by pores having a pore diameter of 10 μm or more and 100 μm or less; and

[0025] The area occupied by pores with a pore diameter of 0.01 μm or more and less than 10 μm (hereinafter referred to as internal pores)

[0026] The internal pores exist with an average thickness of 10 μm or more and 30 μm or less in a direction perpendicular to the surface of the carbon sheet.

[0027] Effects of the Invention

[0028] According to the present invention, a gas diffusion layer capable of improving power generation performance when used in a fuel cell can be obtained by achieving a balance between oxygen permeability in the in-plane direction of the gas diffusion layer and electrical conductivity in a direction perpendicular to the plane of the gas diffusion layer, which was difficult to achieve conventionally. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic cross-sectional view for illustrating the structure of the gas diffusion layer of the present invention.

[0030] Figure 2 This is a schematic cross-sectional view for illustrating a membrane electrode assembly using the gas diffusion layer of the present invention.

[0031] Figure 3 This is a schematic diagram for explaining a method for measuring the in-plane oxygen permeability coefficient A of the gas diffusion layer of the present invention. DETAILED DESCRIPTION

[0032] The carbon sheet and the gas diffusion layer, which are components of the present invention, will be described in detail.

[0033] Hereinafter, the configuration of the gas diffusion layer in the present invention will be described with reference to the drawings. Figure 1 It is a schematic cross-sectional view showing an example of the gas diffusion layer of the present invention.

[0034] exist Figure 1 In the example (a), the gas diffusion layer has a layered internal pore body 4 inside the carbon sheet 1 on the side of one surface 2 (plane X) of the carbon sheet 1, and has a microporous body 5 outside the plane X. The layered internal pore body 4 inside the carbon sheet 1 means that the layered internal pore body 4 exists in the void portion of the carbon sheet 1 which is a porous body. The internal pore body will be described later.

[0035] exist Figure 1 In the example (b), the gas diffusion layer has internal pores 4 in a non-uniformly distributed state inside the carbon sheet 1 on one surface 2 (surface X) side of the carbon sheet 1, and has microporous bodies 5 on the outside of the surface X. The so-called internal pores 4 in a non-uniformly distributed state inside the carbon sheet 1 means that the part where the internal pores 4 exist and the part where the internal pores 4 do not exist are mixed in the void part of the carbon sheet 1 which is a porous body. In this case, the part where the internal pores 4 exist may exist discretely and discontinuously, or may exist continuously in a mesh shape. It should be noted that Figure 1 (b) is closer to the actual form.

[0036] Figure 2 This is an example of a membrane electrode assembly using the gas diffusion layer of the present invention. The membrane electrode assembly of this example has catalyst layers 6a and 6b arranged on both sides of the electrolyte membrane 7, and the gas diffusion layers 0a and 0b of the present invention are stacked in such a way that the microporous layers 5a and 5b are in contact with the catalyst layers 6a and 6b. Figure 2Although not shown in the figure, the separator is provided on the surface 3 (surface Y) side of the carbon sheet 1 opposite to the surface 2 (surface X).

[0037] In the case of the gas diffusion layer of the present invention, when a region of the aforementioned gas diffusion layer having a width of 10 mm and a depth of 3 mm selected arbitrarily is compressed at 0.5 MPa in a direction perpendicular to the surface from one side, the "in-plane oxygen permeability coefficient" of oxygen permeating from the inside of the gas diffusion layer in the in-plane direction is set to A, the "resistance" when the aforementioned gas diffusion layer is compressed at 2 MPa in a direction perpendicular to the surface is set to B, and the number obtained by subtracting 60 and multiplying B from A and adding 310 is set as an index C of compatibility between the in-plane oxygen permeability coefficient and the resistance, the relationship of C being greater than 0 is satisfied, that is, the gas diffusion layer of the present invention can show good power generation performance by satisfying the following formula.

[0038] C = (in-plane oxygen permeability coefficient) - (conductive resistance when pressurized in the direction perpendicular to the plane) × 60 + 310 ≥ 0

[0039] In order to obtain better power generation performance, C is preferably 10 or more, and in order to obtain extremely good power generation performance, C is preferably 20 or more and 200 or less. It should be noted that the plane perpendicular direction refers to the direction perpendicular to the plane (thickness direction).

[0040] Hereinafter, the gas diffusion layer of the present invention will be described in detail.

[0041] [Carbon sheet]

[0042] The carbon sheet used in the gas diffusion layer of the present invention can be made by a process including the preparation of a porous body including carbon fiber or its precursor described later, impregnation with a resin composition, heat treatment, and carbonization. Here, in the case where the resin composition is not included, the impregnation process can also be deleted. In addition, the carbon sheet can be made into a gas diffusion layer by stacking microporous layers. During the above processing, the formation of an internal pore body and / or water repellent processing can also be performed as needed.

[0043] In the present invention, a porous sheet including carbonized carbon fibers, a binder, and, when an internal porous body precursor is formed before a carbonization or graphitization step, the precursor is referred to as a carbon sheet.

[0044] Furthermore, it is important that the carbon sheet used in the gas diffusion layer of the present invention is porous. By making the carbon sheet porous, both excellent gas diffusivity and drainage can be achieved. In order to make the carbon sheet porous, a porous body is preferably used as the material for making the carbon sheet.

[0045] In the present invention, the so-called bonding material refers to a material that plays a role in bonding carbon fibers to each other. The bonding material includes a carbide of a resin composition. In addition, when a water repellent is used for the carbon sheet used in the gas diffusion layer of the present invention, the water repellent is included in the bonding material.

[0046] Next, the porous body used to make the carbon sheet is described. For the carbon sheet used in the gas diffusion layer of the present invention, it is crucial to have high gas diffusivity for diffusing the gas supplied from the diaphragm to the catalyst, high drainage for discharging the water generated with the electrochemical reaction to the diaphragm, and high conductivity for extracting the generated current. Therefore, it is preferred to use a porous body with conductivity and an average pore diameter of 10 to 100 μm. Regarding the porous body used to make the carbon sheet, more specifically, a preferred method is to use a porous body containing carbon fibers such as carbon fiber fabrics, carbon fiber papermaking bodies, and carbon fiber nonwoven fabrics. Among them, from the perspective of excellent corrosion resistance, it is preferred to use a porous body containing carbon fibers in order to obtain a carbon sheet, and from the perspective of excellent "spring property" that makes the characteristic of dimensional changes in the direction perpendicular to the surface of the electrolyte membrane (thickness direction), it is preferred to use a "carbon paper" made by bonding a carbon fiber papermaking body with a carbide as a carbon sheet. In addition, "carbon cloth" which is a woven fabric of carbon fibers and "carbon nonwoven fabric" which is a felt type of carbon fiber nonwoven fabric can also be used. Hereinafter, a carbon fiber papermaking body will be described as a representative example.

[0047] In the present invention, the carbon sheet formed by bonding a carbon fiber paper sheet with a binder can also be obtained by impregnating a carbon fiber paper sheet with a resin composition and carbonizing the impregnated carbon fiber paper sheet as described below.

[0048] As carbon fibers used in the carbon sheet material and the porous body for obtaining the carbon sheet material in the gas diffusion layer of the present invention, polyacrylonitrile (PAN)-based, pitch-based, and rayon-based carbon fibers can be cited. Among them, PAN-based carbon fibers and pitch-based carbon fibers are preferably used in view of excellent mechanical strength.

[0049] With respect to the carbon fibers in the carbon sheet used in the gas diffusion layer of the present invention, the average diameter of the single fibers is preferably in the range of 3 to 20 μm, more preferably in the range of 5 to 10 μm. As a preferred range, it may also be a combination of any of the above upper limits and any of the lower limits. If the average diameter of the single fibers is 3 μm or more, the pore diameter becomes larger and the drainage property improves. On the other hand, if the average diameter of the single fibers is 20 μm or less, when used as a fuel cell, the water vapor diffusion becomes smaller, and the water vapor diffusion becomes smaller. As a result, when it is operated at a higher temperature of 80°C or more, the following problems can be suppressed: the electrolyte membrane dries, the proton conductivity decreases, and the power generation performance decreases as a result.

[0050] Here, the average diameter of a single fiber in a carbon fiber refers to the value obtained by magnifying the carbon fiber to 1000 times and taking a picture with a microscope such as a scanning electron microscope, randomly selecting 30 different single fibers, measuring their diameters, and finding the average value. As a scanning electron microscope, S-4800 manufactured by Hitachi, Ltd. or its equivalent can be used.

[0051] The average length of the single fiber of the carbon fiber used in the present invention is preferably in the range of 3 to 20 mm, more preferably in the range of 5 to 15 mm. If the average length is 3 mm or more, the mechanical strength, electrical conductivity and thermal conductivity of the carbon sheet are excellent. On the other hand, if the average length of the single fiber is 20 mm or less, the dispersion of the carbon fiber during papermaking is excellent, and a homogeneous carbon sheet is obtained. Carbon fibers having such an average length of single fibers are obtained by cutting continuous carbon fibers into a desired length, etc.

[0052] Here, the average length of a single fiber of carbon fiber refers to the value obtained by magnifying the carbon fiber to 50 times and taking a photo with a microscope such as a scanning electron microscope, randomly selecting 30 different single fibers, measuring their lengths, and finding the average value. As a scanning electron microscope, S-4800 manufactured by Hitachi, Ltd. or its equivalent can be used.

[0053] The average diameter and average length of the carbon single fibers in the carbon sheet are usually measured by directly observing the carbon fibers serving as the raw material, but can also be measured by observing the carbon sheet.

[0054] For the purpose of isotropically maintaining the in-plane electrical conductivity and thermal conductivity, the paper body formed by papermaking as one mode for obtaining a porous body of a carbon sheet is preferably a sheet in which carbon fibers are randomly dispersed in a two-dimensional plane. The papermaking process of the carbon fibers when obtaining the carbon fiber paper body may be performed only once or may be performed by laminating multiple times.

[0055] In the present invention, the weight per unit area of ​​the carbon fiber in the carbon fiber papermaking body is preferably 10 to 50 g / m2 In the range of 15 to 35 g / m 2 In the range of 20 to 30 g / m 2 It should be noted that the preferred range may also be a combination of any of the upper limits and any of the lower limits. If the unit area weight of the carbon fiber in the carbon fiber papermaking body is 10 g / m 2 If the carbon fiber papermaking body has a unit area weight of 50 g / m 2 Next, the carbon sheet obtained from the carbon fiber paper body has excellent gas diffusion and drainage properties in the plane direction. When a carbon fiber paper body is prepared by laminating a plurality of paper bodies, the weight per unit area of ​​the carbon fibers of the laminated carbon fiber paper body is preferably within the above range.

[0056] <Impermeation with resin composition>

[0057] When obtaining the carbon sheet used in the gas diffusion layer of the present invention, it is preferred that a porous body containing carbon fibers, such as a carbon fiber papermaking body, is impregnated with a resin composition serving as a binder.

[0058] In the present invention, the bonding material in the carbon sheet is a material that mainly plays the role of bonding carbon fibers to each other, and as the bonding material, a carbide of a resin composition is used. The material in the pre-stage of making a carbon sheet, in which the resin composition that will become the bonding material is impregnated in a porous body containing carbon fibers, is called a "prepreg". The carbon sheet used in the gas diffusion layer of the present invention can be obtained from a prepreg. As a method for making a prepreg by impregnating a porous body containing carbon fibers with a resin composition that will become a bonding material, a method for impregnating a porous body in a solution containing a resin composition, a method for applying a solution containing a resin composition to a porous body, and a method for overlapping and transferring a film formed by a resin composition to a porous body, etc. can be used. Among them, from the perspective of making productivity excellent, it is particularly preferred to use a method in which a porous body is impregnated in a solution containing a resin composition.

[0059] The resin composition used when making the prepreg is preferably a resin composition that is carbonized into a conductive carbide during firing in a subsequent process and functions as a bonding material. The resin composition used when making the prepreg can be a resin composition in which a solvent or the like is added as needed to the resin component. Here, the so-called resin component includes resins such as thermosetting resins, and further includes additives such as carbon powder and surfactants as needed.

[0060] In the present invention, as the resin of the resin component in the resin combination used when making the prepreg, thermosetting resins such as phenolic resin, epoxy resin, melamine resin and furan resin can be listed.Wherein, from the aspect that makes the carbonization yield high, preferably use phenolic resin.In addition, also can not make the resin combination carbonization and use as binding material, can use thermoplastic resins such as fluororesin, ABS resin, polyethylene resin, acrylic resin, nylon resin, polypropylene resin, polyethylene terephthalate resin, polyurethane resin.

[0061] In addition, as the resin component in the resin composition used when making the prepreg, for the purpose of improving the mechanical properties, electrical conductivity and thermal conductivity of the carbon sheet, carbon powder can be used as an additive added as needed. Here, as carbon powder, carbon black, carbon nanotubes, carbon nanofibers, cellulose, chitin fibers (chitin), aramids and other fine fibers such as carbides, milled fibers of carbon fibers (milled fiber), graphite, flake graphite, etc. can be used. Wherein, in order to form a high void pore portion in the surface layer, carbon nanotubes, carbon nanofibers, cellulose, chitin fibers, aramids and other fine fibers such as carbides, milled fibers of carbon fibers can be preferably used.

[0062] The resin composition used in making the prepreg may also be the resin component mentioned above used directly in its original state, and may contain various solvents as needed for the purpose of improving the impregnation of the carbon fiber papermaking body in the porous body. Here, methanol, ethanol, isopropyl alcohol, etc. can be used as the solvent.

[0063] The resin composition used to prepare the prepreg is preferably liquid at 25°C and 0.1 MPa. If the resin composition is liquid under the above conditions, it has excellent impregnation properties in the papermaking body, and the obtained carbon sheet has excellent mechanical properties, electrical conductivity, and thermal conductivity.

[0064] In the present invention, the resin component is preferably impregnated in an amount of 30 to 400 parts by mass, more preferably 50 to 300 parts by mass, relative to 100 parts by mass of carbon fiber in the prepreg. It should be noted that the preferred range may also be a combination of any one of the above upper limits and any one of the lower limits. If the impregnation amount of the resin component relative to 100 parts by mass of carbon fiber in the prepreg is 30 parts by mass or more, the mechanical properties, electrical conductivity and thermal conductivity of the carbon sheet are excellent. On the other hand, if the impregnation amount of the resin component is 400 parts by mass or less, the gas diffusivity in the in-plane direction and the gas diffusivity in the direction perpendicular to the surface of the carbon sheet are excellent.

[0065] <Heat treatment>

[0066] In the present invention, after forming a prepreg in which a porous body such as a carbon fiber papermaking body is impregnated with the resin composition, the prepreg may be heat-treated before carbonization.

[0067] The purpose of the heat treatment in the present invention is to increase the viscosity and cure the resin composition in the prepreg. Examples of the heat treatment method include a method of spraying hot air, a method of heating by clamping on a hot plate such as a pressurizing device, and a method of heating by clamping on a continuous conveyor.

[0068] <Carbonization>

[0069] In the present invention, in order to carbonize the prepreg formed by impregnating the resin composition into a porous body such as a carbon fiber papermaking body, it is fired in an inert atmosphere. The firing can be performed using an intermittent heating furnace or a continuous heating furnace. In addition, an inert atmosphere can be formed by circulating an inert gas such as nitrogen or argon into the furnace.

[0070] In the present invention, the maximum firing temperature is preferably in the range of 1300 to 3000°C, more preferably in the range of 1700 to 3000°C, and further preferably in the range of 1900 to 3000°C. It should be noted that the preferred range may also be a combination of any one of the above upper limits and any one of the lower limits. If the maximum temperature is above 1300°C, carbonization of the resin component in the prepreg is carried out, so that the electrical conductivity and thermal conductivity of the carbon sheet are excellent. On the other hand, if the maximum temperature is below 3000°C, the energy consumption generated by the operation of the heating furnace can be reduced.

[0071] In the present invention, a material obtained by impregnating a porous material such as a carbon fiber papermaking material with a resin composition and then carbonizing the material is sometimes described as a "carbon fiber burnt body." That is, a carbon sheet generally refers to a carbon fiber burnt body, and the carbon fiber burnt body belongs to the carbon sheet regardless of whether or not it is subjected to water repellent treatment.

[0072] <Water-repellent treatment>

[0073] In the present invention, the water-repellent processing of the carbon sheet is carried out for the purpose of improving drainage, which can be implemented by performing water-repellent processing on the carbon fiber sintered body. In this case, the water-repellent processing can be performed by applying a water-repellent agent on the carbon fiber sintered body and performing heat treatment. As another method for water-repellent processing of the carbon sheet, there is a method in which the carbon sheet is not directly subjected to water-repellent processing. This method is not to apply a water-repellent agent on the aforementioned sintered body, but can adopt, for example, the following method: the microporous layer precursor coating liquid is applied to the carbon sheet and then heat-treated, thereby causing the water-repellent contained in the aforementioned coating liquid to move to the carbon sheet for water-repellent processing. In the case of directly applying a water-repellent agent on the carbon sheet, a carbon sheet containing a water-repellent agent as a binding material can be made by performing water-repellent processing. It should be noted that in the case of using a water-repellent agent for water-repellent processing, the aforementioned water-repellent agent can be contained in the carbon sheet as a binding material.

[0074] Here, as the water repellent, from the perspective of achieving excellent corrosion resistance, it is preferred to use a fluorine-based polymer. Examples of the fluorine-based polymer include polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA).

[0075] On the other hand, since the fluorine-based water repellent has insulating properties, the water repellent is thinly attached to the surface of the fired carbon sheet, so that both water repellency and conductivity with the conductive diaphragm can be good. The melting point of the water repellent used in the water repellent process is preferably above 150°C and below 400°C, thereby effectively melting the resin and drying the carbon sheet after the resin is attached, and more preferably above 200°C and below 320°C, so that when the resin is melted, the resin can be uniformly wetted and extended to the carbon fiber papermaking body. It should be noted that as a preferred range, it can also be a combination of any upper limit value and any lower limit value mentioned above.

[0076] As the type of such water repellent, FEP or PFA can be cited. By using these materials, the drainage of the carbon sheet having the structure used in the present invention can be significantly increased, and the accumulation of water inside the water-repellent processed carbon sheet can be reduced, so the diffusion of gas can also be greatly improved. Therefore, the power generation performance is greatly improved.

[0077] The coating amount of the water repellent is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, relative to 100 parts by mass of the carbon fiber sintered body. It should be noted that as a preferred range, it can also be a combination of any upper limit value and any lower limit value mentioned above. If the coating amount of the water repellent is 1 part by mass or more, the drainage of the carbon sheet is excellent. On the other hand, if the coating amount is 50 parts by mass or less, the conductivity of the carbon sheet is excellent.

[0078] In the above-mentioned water-repellent processing, the carbon fiber sintered body can be heat-treated after the water-repellent is applied to the carbon fiber sintered body and then the precursor coating liquid of the microporous layer is applied. As described later, it is preferred that the aforementioned coating liquid also contains a water-repellent. In this case, when the aforementioned coating liquid is applied to the carbon sheet, the water-repellent in the microporous layer precursor coating liquid moves to the carbon sheet. Therefore, the amount of water-repellent possessed by the carbon sheet after heat treatment is determined based on the total amount of the water-repellent contained in the carbon sheet before the aforementioned coating liquid is applied and the water-repellent contained in the aforementioned coating liquid that moves to the carbon sheet. Surface Y ( Figure 1 In the mark 3), the less the amount of water repellent on the surface of the carbon fiber in contact with the diaphragm, the smaller the contact resistance, and a gas diffusion layer with good conductivity can be obtained. In addition, the less the amount of water repellent on the carbon fiber inside the carbon sheet, the smaller the contact resistance between the carbon fibers, so a gas diffusion layer with good conductivity can be obtained. Here, as mentioned above, there is a phenomenon that the water repellent in the coating liquid moves to the carbon sheet when the microporous layer precursor coating liquid is applied to the carbon sheet. At this time, the water repellent diffuses due to the concentration gradient, so the concentration of the water repellent at the destination of movement is uniformly maintained. Therefore, a small amount of water repellent can be used to give the gas diffusion layer sufficient water repellency. Therefore, for the purpose of improving the conductivity of the gas diffusion layer, the amount of water repellent on the carbon fiber of surface Y can be reduced, and as an indicator for controlling the conductivity of the carbon sheet, the amount of water repellent attached to the carbon sheet of the gas diffusion layer can be used. When a fluorine-based polymer is used as a water repellent, the ratio of the number of fluorine atoms to the number of carbon atoms on the carbon sheet can be used as an indicator of the amount of water repellent attached to the carbon sheet. In the present invention, it is preferably in the range of 0.002 or more and 0.030 or less, and more preferably in the range of 0.003 or more and 0.030 or less. The aforementioned fluorine atom ratio can be determined by X-ray microanalysis using secondary electrons, and can be obtained by the following method: the fluorine atom number concentration and the carbon atom number concentration on the surface of the carbon fiber on the surface Y are measured at 10 randomly selected different locations, and the ratio is averaged.

[0079] <Formation of microporous layer>

[0080] Next, the microporous layer which is one of the components of the present invention will be described.

[0081] The carbon sheet used in the gas diffusion layer of the present invention can be used as a gas diffusion layer by forming a microporous layer on one surface. Furthermore, the gas diffusion layer of the present invention has a microporous layer on at least the surface X of the carbon sheet.

[0082] In the present invention, the weight per unit area of ​​the microporous layer is preferably 10 to 30 g / m 2 If the unit area weight of the microporous layer is 10 g / m 2When the precursor coating liquid of the microporous layer is applied to the carbon sheet, the coating liquid easily penetrates from the surface of the carbon sheet in a direction perpendicular to the surface, and forms a microporous layer inside the carbon sheet, and the microporous layer becomes an internal pore body. In addition, if the unit area weight of the microporous layer is 30 g / m 2 In order to control the existence range of the microporous layer inside the gas diffusion layer, that is, the internal pores, the unit weight of the microporous layer including the internal pores is more preferably 10 to 20 g / m 2 It should be noted that, as a preferred range, it may also be a combination of any upper limit value and any lower limit value mentioned above.

[0083] In the present invention, the microporous layer preferably contains conductive particles. From the viewpoint of corrosion resistance, it is further preferred that the conductive particles contain carbon powder. In addition, from the viewpoint of improving conductivity and drainage, a porous body containing linear carbon and a water repellent in the microporous layer can be used. As carbon powder in the conductive particles, carbon blacks such as furnace black, acetylene black, lamp black and thermal black can be listed; graphites such as flaky graphite, flaky graphite, earthy graphite, artificial graphite, expanded graphite and flake graphite; carbon powders such as CNT. Among them, carbon black is more preferably used, and acetylene black is most preferably used from the perspective of reducing impurities.

[0084] In the present invention, the porosity of the internal pore body is preferably in the range of 80% or more and 95% or less. More preferably, it is 85% or more and 95% or less. If the porosity of the aforementioned microporous layer is 85% or more, the gas diffusion in the plane direction is promoted, the gas diffusivity can be improved, and the drainage from the gas diffusion layer can be improved. In addition, if the porosity of the microporous layer is 95% or less, the reverse diffusion of the gas is promoted, so when the fuel cell is operated at a high temperature of 80°C or more, the problem of drying of the electrolyte membrane and decreased proton conductivity can be suppressed.

[0085] In the present invention, from the viewpoint of promoting drainage of water in liquid state, a preferred mode is to include a water repellent in the microporous layer. Wherein, from the aspect of making excellent corrosion resistance, it is preferred to use a fluorine-based polymer as a water repellent. As a fluorine-based polymer, polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP) and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) etc. can be listed.

[0086] The microporous layer can be formed by applying a conductive particle-containing coating liquid containing the above-mentioned conductive particles onto the surface of the carbon sheet.

[0087] The coating liquid containing conductive particles may contain a dispersion medium such as water or an organic solvent, and may also contain a dispersion aid such as a surfactant. As the dispersion medium, water is preferred, and the dispersion aid is preferably a nonionic surfactant. In addition, various carbon powders and water repellents as described above may also be contained.

[0088] The coating liquid containing conductive particles can be applied to the carbon sheet using various commercially available coating devices. As the coating method, screen printing, rotary screen printing, spray coating, gravure printing, gravure printing, die coater coating, rod coating, and blade coating can be used. The above coating methods are only examples and are not necessarily limited to these coating methods.

[0089] It is preferred that: after the coating liquid containing conductive particles is applied to the carbon sheet, the coating liquid is dried at a temperature of 80 to 180°C. That is, the coating is placed in a dryer set at a temperature of 80 to 180°C and dried in a range of 5 to 30 minutes. The drying air volume can be appropriately determined, but rapid drying sometimes induces micro cracks on the surface. It is preferred that: after the coating is dried, it is placed in a muffle furnace, a sintering furnace or a high-temperature dryer, and heated at a temperature preferably of 300 to 380°C for 5 to 20 minutes to melt the water repellent and become a binder between conductive particles such as carbon powder, thereby forming a microporous layer.

[0090] <Internal pore body>

[0091] In the present invention, if Figure 1 As shown in (a), a preferred embodiment is to include an internal pore body 4 having a pore diameter of 0.01 μm or more and less than 10 μm in the form of a layered region having an average thickness shown by a mark 12 near the inner surface of the surface 2 (surface X) side of the carbon sheet 1. In addition, as another preferred embodiment, the following embodiments can be cited: Figure 1As shown in (b), the internal pore body 4 having a pore diameter of 0.01 μm or more and less than 10 μm is included in a non-uniformly distributed state near the surface inside the surface 2 (surface X) side of the carbon sheet 1. In the case of adopting the above method, the range of the internal pore body filled near the surface inside the surface 2 (surface X) side of the carbon sheet 1 is averaged, and the obtained value is defined as the average thickness 12 of the internal pore body. In the carbon sheet, the region containing carbon fibers mainly has voids with a pore diameter of 10 μm or more and 100 μm or less, and the internal pore body has the above pore diameter. It is important that the internal pore body exists in the range from the surface of the carbon sheet to the appropriate position in the perpendicular direction of the surface. The average thickness 12 is preferably in the range of 10 μm or more and 30 μm or less in the perpendicular direction from the surface of the aforementioned carbon sheet, more preferably 12 to 25 μm, and more preferably 15 to 25 μm. It should be noted that as a preferred range, it can also be a combination of any of the above upper limits and any of the above lower limits. If the aforementioned range is 10 μm or more, the conductive path inside the aforementioned carbon sheet increases, and the conductivity is improved. In addition, if the aforementioned range is 30 μm or less, a gas permeation path is well formed inside the aforementioned carbon sheet, and the gas diffusion is improved. It should be noted that the location and thickness of the internal pores can be determined by taking a photograph of a vertical cross-section of the surface of the carbon sheet or the gas diffusion layer at a high magnification and observing the aforementioned photograph.

[0092] The aforementioned internal pore body has a small pore diameter, so it has the effect of improving the conductivity between carbon fibers and can reduce the resistance of the gas diffusion layer. In the manufacturing process of the carbon sheet, the precursor coating liquid of the internal pore body is applied to the side of the carbon sheet that will become the surface X before the firing process, so that the internal pore body can be formed. In this case, since the internal pore body is formed before the microporous layer precursor coating liquid is applied to the carbon sheet, the phenomenon of excessive penetration of the microporous layer precursor coating liquid into the carbon sheet can be suppressed. As a result, the gas permeability in the carbon sheet can be improved. In the present invention, when the internal pore body precursor is formed before the carbonization of the carbon sheet, the carbon fiber fired body including the internal pore body is also equivalent to a "carbon sheet". In addition, the aforementioned internal pore body can also be formed by applying the precursor coating liquid of the internal pore body after the carbon sheet is manufactured. In this case, the microporous layer precursor coating liquid can also be used as the precursor coating liquid of the internal pore body at the same time. The unit area weight of the carbon sheet internal pore body is preferably 3g / m 2 Above, 15g / m 2 The following range, more preferably 5g / m 2 Above, 12g / m 2 It should be noted that a preferred range may be a combination of any one of the upper limits and any one of the lower limits described above.

[0093] When an internal pore body is formed in the manufacturing process of the carbon sheet, a resin composition formed by a mixture of a material that becomes conductive particles after firing and a resin that becomes a binder after firing can be used as the internal pore body precursor coating liquid, and as the material that becomes conductive particles after firing, carbon black, carbon nanotubes, carbon nanofibers, cellulose, chitin fibers, aramid and other fine fibers and / or their carbides, ground fibers of carbon fibers, graphite, flake graphite, etc. can be used. Among them, in order to form a high-void internal pore body, carbon nanotubes, carbon nanofibers, cellulose and / or chitin fibers and / or aramid and other fine fibers carbides, and ground fibers of carbon fibers can be preferably used.

[0094] [Characteristics of Carbon Sheet]

[0095] The characteristics of the carbon sheet used in the gas diffusion layer of the present invention obtained by the above-described steps will be described.

[0096] In the present invention, when the range from the surface of the carbon sheet having the microporous layer (surface X) to a position 20 μm in the perpendicular direction to the surface is defined as the surface layer, the density of the surface layer of the carbon sheet is preferably 0.34 g / cm 3 The upper limit is preferably 0.80 g / cm 3 The overall density of the carbon sheet is preferably 0.29 / cm 3 Above, 0.33g / cm 3 That is, in the preferred embodiment of the carbon sheet used in the present invention, it is important that the density of the surface layer of the carbon sheet is higher than the density of the entire carbon sheet. If the density of the surface layer is 0.34 g / cm 3 As the pore size of the carbon sheet tends to become smaller, the thickness of the internal pores in the carbon sheet in the perpendicular direction can be controlled to the range described below. In addition, the microporous layer can cover the surface of the carbon sheet, which can suppress the possibility of carbon fibers protruding from the microporous layer, and improve the surface quality. Moreover, the conductivity is high, and the power generation performance is improved in both high and low temperature conditions. If the overall density of the carbon sheet is 0.29g / cm 3 As described above, a conductive path is formed in the carbon sheet, and the conductivity of the gas diffusion layer using the carbon sheet is improved. On the other hand, if the density of the entire carbon sheet is 0.33 g / cm 3 Then, appropriate voids are formed in the carbon sheet, and the gas diffusion property of the gas diffusion layer using the carbon sheet is improved.

[0097] The carbon sheet having the above-mentioned density can be obtained by controlling the weight per unit area of ​​the carbon fiber in the prepreg, the amount of the resin component relative to the carbon fiber, and the thickness of the carbon sheet as described in the method for preparing the carbon sheet described later. Here, the density of the carbon sheet can be obtained by dividing the weight per unit area (mass per unit area) of the carbon sheet obtained by weighing with an electronic balance by the thickness of the carbon sheet when pressed at a surface pressure of 0.15 MPa.

[0098] In addition, the thickness of the carbon sheet used in the gas diffusion layer of the present invention is preferably 50 to 230 μm, more preferably 70 to 180 μm, and further preferably 90 to 130 μm. It should be noted that the preferred range may also be a combination of any of the above upper limits and any of the lower limits. By making the thickness of the carbon sheet 230 μm or less, more preferably 180 μm or less, and further preferably 130 μm or less, the diffusivity of the gas is easily increased, and the generated water is also easily discharged. Furthermore, the size of the fuel cell as a whole is also easily reduced. On the other hand, by making the thickness of the carbon sheet 50 μm or more, more preferably 70 μm or more, and further preferably 90 μm or more, the gas diffusion in the in-plane direction inside the carbon sheet can be efficiently carried out, and the power generation performance becomes easy to improve.

[0099] It should be noted that the thickness of the carbon sheet used in the gas diffusion layer of the present invention is determined by the following method. That is, the carbon sheet and the gas diffusion layer are placed on a smooth platform and the thickness is measured under a pressure of 0.15 MPa. Samples are taken from 10 different locations, and the average of the measured values ​​is used as the thickness.

[0100] When measuring the surface density of the carbon sheet, first, a cross section of the gas diffusion layer is formed by ion cutting, and the position of the surface X of the carbon sheet is determined by observation using SEM. Next, for the SEM image of the above cross section, the range from surface X to a depth of 20 μm is set as the surface layer, the area of ​​the material filling region in the surface layer is calculated, and then the material filling rate is calculated by dividing the filling area by the area of ​​the surface layer. The value obtained by multiplying the above filling rate by the density of the filled material is set as the surface density. It should be noted that the carbon sheet can also be separated from the gas diffusion layer. For example, the gas diffusion layer is heated at 600°C in the atmosphere for 30 minutes to oxidatively decompose the resin composition contained in the microporous layer in the gas diffusion layer, and then ultrasonic treatment is performed in ethanol to remove the carbon sheet.

[0101] <Membrane electrode assembly>

[0102] In the present invention, the aforementioned gas diffusion layer is bonded to the solid polymer electrolyte membrane via the catalyst layer to form a membrane electrode assembly. In this case, by arranging the microporous layer of the gas diffusion layer on the catalyst layer side, it is easier to cause the reverse diffusion of the generated water, and the contact area between the catalyst layer and the gas diffusion layer is increased, which can reduce the contact resistance.

[0103] <Fuel Cell>

[0104] The fuel cell of the present invention comprises the gas diffusion layer of the present invention, and has a diaphragm on both sides of the above-mentioned membrane electrode assembly. That is, a fuel cell is formed by configuring a diaphragm on both sides of the above-mentioned membrane electrode assembly. Usually, a solid polymer fuel cell is formed by stacking a plurality of components that clamp both sides of such a membrane electrode assembly with a diaphragm separated by a gasket. The catalyst layer is composed of a layer containing a solid polymer electrolyte and carbon supporting the catalyst. Platinum is usually used as a catalyst. In a fuel cell that supplies a modified gas containing carbon monoxide to the anode side, platinum and ruthenium are preferably used as catalysts on the anode side. The solid polymer electrolyte preferably uses a perfluorosulfonic acid-based polymer material with high proton conductivity, oxidation resistance and heat resistance. The structure of such a fuel cell unit and fuel cell itself is known.

[0105] Example

[0106] Next, the gas diffusion layer of the present invention will be specifically described using examples, but the present invention is not limited to these examples.

[0107] The following describes the materials used in the examples, methods for producing the carbon sheet and the gas diffusion layer, and methods for evaluating the gas diffusion layer or the fuel cell.

[0108] <Manufacturing of Carbon Sheets>

[0109] Toray Industries, Inc. polyacrylonitrile carbon fiber "Torayca" (registered trademark) T300 (average carbon fiber diameter: 7 μm) was cut into an average length of 12 mm, dispersed in water, and continuously made into paper using a wet papermaking method. A 10% aqueous solution of polyvinyl alcohol as a binder was then applied to the paper and dried to produce a carbon fiber with a unit area weight of 25 g / m 2 The adhesion amount of polyvinyl alcohol was 22 parts by mass based on 100 parts by mass of the carbon fiber papermaking body.

[0110] Next, a resin composition obtained by mixing Resol-type phenolic resin and Novolac-type phenolic resin as thermosetting resins in a mass ratio of 1:1, flaky graphite (average particle size of 5 μm) as carbon powder, and methanol as a solvent were mixed in a ratio of thermosetting resin / carbon powder / solvent = 10 parts by mass / 5 parts by mass / 85 parts by mass, and stirred for 1 minute using an ultrasonic disperser to obtain a uniformly dispersed resin composition.

[0111] Next, the carbon fiber paper body cut into 15cm×12.5cm is horizontally impregnated with the resin composition filled with an aluminum plate, and is squeezed and impregnated with rollers. At this time, the overall amount of attached resin is adjusted by arranging two rollers horizontally with a certain gap and pulling the carbon fiber paper body vertically upward. The resin composition is squeezed by clamping one side with a smooth metal roller having a structure in which excess resin is removed with a scraper, and the opposite side with a concave-convex gravure roller, thereby adjusting the difference in the amount of resin adhesion on the surface and the back. After impregnation, it is heated at a temperature of 100°C for 5 minutes to dry it and make a pre-impregnated body. Next, while applying pressure with a flat press, heat treatment is performed at a temperature of 180°C for 5 minutes. During pressurization, a spacer is arranged on the flat press at a position further outward than the thickness direction end of the pre-impregnated body to adjust the interval between the upper and lower press panels.

[0112] The substrate subjected to heat treatment of the prepreg was introduced into a heating furnace maintained in a nitrogen atmosphere at a maximum temperature of 2400° C. to produce a carbon sheet (135 μm in thickness) consisting of a carbon fiber sintered body.

[0113] <Water-repellent treatment>

[0114] The carbon sheet prepared as above is immersed in an aqueous dispersion of PTFE resin ("Polyfuron" (registered trademark) PTFE dispersion D-1E (manufactured by Daikin Industries, Ltd.)) or an aqueous dispersion of FEP resin ("Neoflon" (registered trademark) FEP dispersion ND-110 (manufactured by Daikin Industries, Ltd.) as a water repellent, so that the water repellent is impregnated in the carbon fiber sintered body. Then, it is heated in a drying furnace at a temperature of 100°C for 5 minutes and dried to prepare a water-repellent processed carbon sheet. In addition, the aqueous dispersion of the water repellent is diluted to an appropriate concentration for use so that after drying, 0 to 5 parts by mass of the water repellent is imparted to 100 to 95 parts by mass of the carbon sheet.

[0115] In addition, without directly performing the above-mentioned water-repellent treatment on the carbon sheet, in the process of applying the microporous layer precursor coating liquid to the carbon sheet, or in the process of applying the internal pore body precursor coating liquid to the carbon sheet, a microporous layer precursor coating liquid or an internal pore body precursor coating liquid containing a fluorine-based polymer is used to move the fluorine-based polymer into the carbon sheet, thereby performing the water-repellent treatment on the carbon sheet.

[0116] <Production of Gas Diffusion Layer>

[0117] <Materials>

[0118] Carbon powder A: Acetylene black: "DENKA BLACK (registered trademark)" (manufactured by Denkagaku Kogyo Co., Ltd.)

[0119] Carbon powder B: Linear carbon: "VGCF (registered trademark)" (manufactured by Showa Denko K.K.) with an aspect ratio of 70

[0120] Material C: Water repellent: FEP resin ("Neoflon (registered trademark)" FEP dispersion ND-110 (manufactured by Daikin Industries, Ltd.), which is an aqueous dispersion containing 25 parts by mass of FEP resin, was used)

[0121] Material D: Novolac type phenolic resin "Tamanol (registered trademark)" 759 (manufactured by Arakawa Chemical Industries, Ltd.)

[0122] Material E: surfactant "TRITON (registered trademark)" X-100 (manufactured by Nakalai Tesque Co., Ltd.).

[0123] Solvent F: Methanol

[0124] Dispersion medium G: purified water

[0125] The above materials were mixed in accordance with the composition shown in Table 1 using a disperser to prepare a microporous layer precursor coating liquid 1 and internal pore body precursor coating liquids 2 to 4. In addition, the internal pore body precursor coating liquid was applied to the carbon sheet using a slit die coater and carbonized as needed. The microporous layer precursor coating liquid was applied to the carbon sheet to form a planar microporous layer. The coating liquid used here uses a coating liquid in which carbon powder, a water repellent, a surfactant and purified water are adjusted in accordance with the composition of the coating liquid containing conductive particles in parts by mass as shown in Table 1. It should be noted that the amount of FEP resin shown in Table 1 represents the amount of FEP resin itself rather than the amount of the aqueous dispersion of FEP resin. After applying the microporous layer precursor coating liquid to the carbon sheet using a die coater, it was heated at a temperature of 120°C for 10 minutes, and then heated at a temperature of 380°C for 10 minutes to form a microporous layer.

[0126] <Measurement of weight per unit area of ​​microporous layer>

[0127] The unit area weight of carbon sheet and gas diffusion layer [g / m 2 ] The mass of a 10 cm square sample is divided by the area of ​​the sample (0.01 m 2 ) is calculated. In addition, the value obtained by subtracting the weight per unit area of ​​the carbon sheet from the weight per unit area of ​​the gas diffusion layer is defined as the weight per unit area of ​​the microporous layer.

[0128] <Measurement of thickness and density>

[0129] The carbon sheet and the gas diffusion layer were placed on a smooth platform and the thickness was measured under a pressure of 0.15 MPa. Samples were taken from 10 different locations and the average of the measured values ​​was taken as the thickness. In addition, the density [g / cm 3 ].

[0130] <Evaluation of In-plane Oxygen Permeability Coefficient A of Gas Diffusion Layer>

[0131] The water vapor diffusion evaluation device (MVDP-200C) manufactured by Seika Industry Co., Ltd. was used. Figure 3 In the piping system shown, first, only valve A (23) is opened, and nitrogen 33 is allowed to flow into the primary side piping A (22) while valve B (25) is closed. A predetermined amount (190cc / min) of gas is circulated in the mass flow controller (21), and the pressure controller (24) is adjusted so that a gas pressure of 5kPa is applied relative to the atmospheric pressure. A gas diffusion layer (28) is provided on a sealing material (32) having a width of 10mm and a depth of 3mm provided between gas chamber A (27) and gas chamber B (29), and the sealing material is pressurized, thereby compressing the area having a width of 10mm and a depth of 3mm in the gas diffusion layer at 0.5MPa. Next, valve A (23) is closed, valve B (25) is opened, and nitrogen is circulated in piping B (26). The nitrogen gas flowing into the gas chamber A (27) passes through the gaps of the gas diffusion layer (28) and moves to the gas chamber B (29), passes through the pipe C (30), and then passes through the gas flow meter (31) to be released into the atmosphere. The gas flow rate (cc / min) flowing through the gas flow meter (31) at this time is measured, and 90.9% of this value is taken as the in-plane oxygen permeability coefficient A [cc / min (cc / min)] of the compressed area with a width of 10 mm and a depth of 3 mm.

[0132] <Evaluation of resistor B>

[0133] The resistance of the gas diffusion layer was calculated as follows: The gas diffusion layer cut into 2.0 cm × 2.0 cm was sandwiched between two gold-plated plates and a uniform surface pressure of 2.0 MPa was applied. A current of 1.0 A was passed through the thickness direction of the gas diffusion layer. The resistance at this time was measured and multiplied by the electrode area 4 cm 2 The resulting value.

[0134] <Evaluation of the balance between gas diffusibility and electrical conductivity>

[0135] When evaluating the balance between gas diffusivity and electrical conductivity of the gas diffusion layer, the in-plane oxygen permeability coefficient A calculated by the above method and the resistance B under pressure calculated by the above method are used to calculate a number C, which is the number obtained by subtracting 60 multiplied by B from A and adding 310.

[0136] <Determination of the ratio of the number of fluorine atoms to the number of carbon atoms>

[0137] In the gas diffusion layer, 10 different locations were randomly selected from the carbon fiber on the surface opposite to the surface on which the microporous layer was formed, and the locations were magnified to 2000 times using a scanning electron microscope at an accelerating voltage of 7 kV, and the number of fluorine atoms and the number of carbon atoms were measured by point analysis, and the value obtained by averaging the ratio of the number of fluorine atoms to the number of carbon atoms at the 10 locations was used as the fluorine element / carbon element ratio on the carbon fiber. It should be noted that as a scanning electron microscope, S-3500N manufactured by Hitachi, Ltd. was used, and as an energy dispersive X-ray analyzer, EX-370 manufactured by Horiba, Ltd. was used.

[0138] In addition, the ratio of the number of fluorine atoms to the number of carbon atoms was determined by the same method at 10 different locations randomly selected on the carbon fibers near the center in the thickness direction of the carbon sheet in the gas diffusion layer.

[0139] <Measurement of the porosity and average thickness of internal pores>

[0140] The porosity of the internal pores is determined as follows. First, as a scanning electron microscope, S-3500 manufactured by Hitachi, Ltd. is used. In the vertical section of the surface of the gas diffusion layer, 20 different parts of the internal pores existing inside the carbon sheet are randomly selected, magnified at a magnification of about 2000 times, and photographed. Next, for the 20 images obtained by photographing, the void part and the non-void part are separated respectively, and the area ratio of the void part relative to the total area of ​​the void part and the non-void part is used as the porosity of each image. Finally, the above-mentioned individual porosities in the 20 images are averaged to determine the average porosity. When making the vertical section, an ion milling device IM4000 manufactured by Hitachi High-Technologies Co., Ltd. is used. Even in the case where the structure of the microporous layer is uneven, as long as the above method can be performed, the averaged internal pore porosity [%] can be determined by averaging the samples of 20 random parts. In this case, by finding the area of ​​the region where the internal pores exist, the thickness of the internal pores when it is assumed that the internal pores exist uniformly inside the carbon sheet can be found, and this thickness is taken as the average thickness of the internal pores ( Figure 1 Mark 12 in the figure).

[0141] <Calculation method of unit area weight of internal pores>

[0142] The weight per unit area of ​​the internal pores was calculated by multiplying the density of the internal pores by the average thickness. Here, the porosity of the internal pores and the true density of the material forming the internal pores used in Examples and Comparative Examples, 2.1 g / cm 3 The density of the internal pore body is calculated according to the following formula: The average thickness is the value calculated in the above-mentioned <Measurement of the porosity and average thickness of the internal pore body>.

[0143] Internal pore density [g / cm 3 ]=2.1[g / cm 3 ]×(1-porosity of internal pores [%]÷100)

[0144] <Calculation method of surface density>

[0145] First, 20 vertical sections of the gas diffusion layer were randomly selected, and each section was magnified and observed at a magnification of about 200 times using SEM. Next, in each observed area, the total area of ​​the portion filled with carbon fibers and substances that form internal pores was extracted for the area from the surface of the carbon sheet to a position of 20 μm in the vertical direction. At this time, the material filling rate of the internal pore formation area can be obtained by multiplying the area of ​​the internal pore existence area by the porosity. Next, the material filling rate for the surface area is calculated by multiplying the density of the filling material 2.1 g / cm 3 The obtained value was averaged for 20 locations and was taken as the surface density.

[0146] <Evaluation of Power Generation Performance of Solid Polymer Fuel Cells>

[0147] A catalyst solution was prepared by sequentially adding 1.00 g of platinum-loaded carbon (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., platinum loading: 50 mass %), 1.00 g of purified water, 8.00 g of "Nafion" (registered trademark) solution (5.0 mass % of "Nafion" (registered trademark) manufactured by Aldrich Co.), and 18.00 g of isopropyl alcohol (manufactured by Nakalai Tesque Co., Ltd.).

[0148] Next, the catalyst solution was applied by spraying onto a 5 cm × 5 cm “NAFLON” (registered trademark) PTFE tape “TOMBO” (registered trademark) No. 9001 (manufactured by NICHIAS Co., Ltd.) and dried at room temperature to prepare a platinum-containing tape having a platinum content of 0.3 mg / cm 2 Next, a solid polymer electrolyte membrane "Nafion" (registered trademark) NRE-211CS (manufactured by DuPont) cut into 8 cm × 8 cm was sandwiched between two PTFE sheets with a catalyst layer, and the catalyst layer was transferred to the solid polymer electrolyte membrane while being pressed at 130°C for 5 minutes while being pressurized to 5 MPa with a flat press. After pressing, the PTFE sheet was peeled off to produce a solid polymer electrolyte membrane with a catalyst layer.

[0149] Next, the solid polymer electrolyte membrane with the catalyst layer was sandwiched between two pieces of 5 cm × 5 cm each obtained by cutting the gas diffusion layer produced in each embodiment and comparative example, and pressed at 130° C. for 5 minutes while applying a pressure of 3 MPa using a flat plate press to produce a membrane electrode assembly. The gas diffusion layer was arranged so that the surface having the microporous layer was in contact with the catalyst layer side.

[0150] The obtained membrane electrode assembly was installed in a single cell for fuel cell evaluation, and the current density was measured to be 2.0 A / cm2 Here, as the diaphragm, a serpentine type diaphragm with a single flow path and a groove width, groove depth, and ridge width of 1.0 mm was used. In addition, non-pressurized hydrogen was supplied to the anode side, and non-pressurized air was supplied to the cathode side for evaluation.

[0151] (Example 1)

[0152] According to the above-mentioned <Preparation of Carbon Sheet>, the water repellent was impregnated into the carbon sheet to perform water repellent treatment, and then the microporous layer precursor coating liquid was used according to the method described in <Preparation of Gas Diffusion Layer> to obtain a gas diffusion layer having internal pores. The results showed that the gas diffusion property and the electrical conductivity were well balanced and the power generation performance was good. The results are shown in Table 2.

[0153] (Example 2)

[0154] The same method as in Example 1 was used except that the weight per unit area of ​​the microporous layer was changed to 20 g / m 2 , the thickness of the internal pore body was set to 11 μm, and the gas diffusion layer was obtained by a different method. The results showed that the average thickness of the internal pore body was further optimized, so that the gas permeation path increased and the gas diffusivity was further improved compared with Example 1. In addition, the gas diffusivity and electrical conductivity were well balanced, and the power generation performance was good. The results are shown in Table 2.

[0155] (Example 3)

[0156] The same method as in Example 1 was used except that the weight per unit area of ​​the microporous layer was changed to 5 g / m 2 , reducing the coating gap of the microporous layer precursor coating liquid, and setting the thickness of the internal pore body to 20 μm to obtain a gas diffusion layer. The results show that by further optimizing the weight per unit area of ​​the internal pore body, the gas diffusion property is further improved compared with Example 1. The gas diffusion property and the electrical conductivity are well balanced, and the power generation performance is good. The results are shown in Table 2.

[0157] (Example 4)

[0158] The same method as in Example 1 was used except that the weight per unit area of ​​the microporous layer was changed to 10 g / m 2 The gas diffusion layer was obtained by a different method in which the average thickness of the internal pores was set to 10 μm. As a result, the gas diffusion property and the electrical conductivity were better balanced and the power generation performance was better. The results are shown in Table 2.

[0159] (Example 5)

[0160] Although the method is the same as that in Example 4, the amount of water repellent used in the water repellent treatment of the carbon sheet is reduced, thereby obtaining a gas diffusion layer with a fluorine / carbon ratio of 0.020 on the fiber of surface Y. As a result, the conductivity is improved by further optimizing the amount of water repellent, so that the gas diffusivity and conductivity are better balanced, and the power generation performance is better. The results are shown in Table 2.

[0161] (Example 6)

[0162] Although the method is the same as that in Example 5, the amount of water repellent used in the water repellent treatment of the carbon sheet is further reduced, thereby obtaining a gas diffusion layer with a fluorine / carbon ratio of 0.015 on the back fiber. As a result, the conductivity is further improved by further optimizing the amount of water repellent, and the gas diffusion and conductivity are well balanced, and the power generation performance is very good. The results are shown in Table 2.

[0163] (Example 7)

[0164] Although the method is the same as that of Example 6, the carbon sheet is not impregnated with a water repellent, but the carbon sheet is treated with a water repellent using a microporous layer precursor coating liquid, thereby obtaining a gas diffusion layer with a fluorine / carbon ratio of 0.0050 on the back fiber. As a result, the gas diffusion property and the electrical conductivity are well balanced, and the power generation performance is very good. The results are shown in Table 2.

[0165] (Example 8)

[0166] In the method described in <Preparation of Gas Diffusion Layer>, except that the internal pore body precursor coating liquid 2 was coated on the carbon sheet and the microporous layer precursor coating liquid 1 was coated after drying, the same method as in Example 7 was used to obtain a gas diffusion layer having an internal pore body porosity of 80%. As a result, the gas diffusion property was improved by increasing the porosity. The gas diffusivity and the electrical conductivity were well balanced, and the power generation performance was very good. The results are shown in Table 2.

[0167] (Example 9)

[0168] In the method described in <Preparation of Gas Diffusion Layer>, except that the internal pore body precursor coating liquid 3 was coated on the carbon sheet and the microporous layer precursor coating liquid 1 was coated after drying, a gas diffusion layer having an internal pore body porosity of 90% was obtained by the same method as in Example 7. As a result, although the porosity increased, the average thickness of the internal pore body increased, so the gas diffusivity was not improved compared with Example 8, but the conductivity was improved. The gas diffusivity and conductivity were very good, and the power generation performance was very good. The results are shown in Table 2.

[0169] (Example 10)

[0170] In the method described in <Preparation of Gas Diffusion Layer>, the internal pore body precursor coating liquid 4 was coated on the carbon sheet, dried and carbonized, and then the microporous layer precursor coating liquid 1 was coated. The same method as in Example 7 was used to obtain a gas diffusion layer with an internal pore body porosity of 91%. As a result, the surface layer density was slightly reduced, and the gas diffusion property was further improved compared to Example 9. The gas diffusibility and electrical conductivity were very good, and the power generation performance was very good. The results are shown in Table 2.

[0171] (Example 11)

[0172] The method for making the carbon sheet was changed. First, the long fibers of polyacrylonitrile were subjected to flame retardant treatment at a temperature of 200°C for 10 minutes, and non-woven fabrics were made by water flow interlacing treatment, and roll pressing was performed. The carbon sheet was introduced into a heating furnace at a temperature of 2000°C to obtain a carbon sheet formed by a carbon fiber sintered body of a non-woven fabric with a thickness of 150 μm. Next, the carbon sheet was used to obtain a gas diffusion layer using the same method as in Example 1. The results showed that the gas diffusion property and the electrical conductivity were well balanced and the power generation performance was good. The results are shown in Table 2.

[0173] (Example 12)

[0174] As the carbon sheet, the same nonwoven fabric as that used in Example 11 was used, and the weight per unit area of ​​the inner pores was set to 5 g / m 2 , except for this, a gas diffusion layer was obtained by the same method as in Example 9. The results showed that the gas diffusion property and the electrical conductivity were well balanced and the power generation performance was well. The results are shown in Table 2.

[0175] (Example 13)

[0176] The same method as in Example 1 was used, but the weight per unit area of ​​the internal pores was set to 5 g / m 2 , and the weight per unit area of ​​the microporous layer is set to 5 g / m 2 The gas diffusion layer was obtained. As a result, although high gas diffusivity was obtained, the conductivity was slightly reduced due to the reduction in the weight per unit area of ​​the microporous layer. The gas diffusivity and conductivity were well balanced, and the power generation performance was good. The results are shown in Table 2.

[0177] (Example 14)

[0178] The same method as in Example 2 was used, but the weight per unit area of ​​the microporous layer was increased to 25 g / m 2On the other hand, the gap during the coating process of the microporous layer precursor was enlarged to obtain a gas diffusion layer with an average thickness of 30 μm of internal pores. The results showed that the gas diffusion property and the electrical conductivity were well balanced and the power generation performance was good. The results are shown in Table 2.

[0179] (Example 15)

[0180] Although the method is the same as that of Example 14, the coating gap of the microporous layer precursor coating liquid is reduced compared with Example 14, and the average thickness of the internal pore body is increased to 26 μm. The results show that the gas diffusion layer has good compatibility with the electrical conductivity and good power generation performance. The results are shown in Table 2.

[0181] (Comparative Example 1)

[0182] Compared with Example 1, the coating gap of the microporous layer precursor coating liquid was reduced to make the average thickness of the internal pore body 33 μm. The gas diffusion layer was obtained by the same method as Example 1. The results showed that the gas diffusion property and the electrical conductivity were poorly balanced and the power generation performance was low. The results are shown in Table 2.

[0183] (Comparative Example 2)

[0184] Compared with Example 1, the carbon fiber unit area weight was set to 29 g / m 2 The gas diffusion layer was obtained in the same manner as in Example 1 except that a high-density carbon sheet was prepared. The results showed that the gas diffusion property and the electrical conductivity were not compatible and the power generation performance was low. The results are shown in Table 2.

[0185] (Comparative Example 3)

[0186] Compared with Example 1, the microporous layer precursor coating liquid was made with a unit area weight of 13 g / m 2 Apply on release paper and dry at 100°C to obtain a dried microporous layer precursor. The dried microporous layer precursor is overlapped on the carbon sheet and pressurized, and the release paper is peeled off at 120 degrees to transfer the dried microporous layer precursor to the carbon sheet, and heated in the atmosphere at 380°C for 10 minutes to obtain a gas diffusion layer. Using this method, the average thickness of the internal pores becomes smaller and is 3μm. In addition, the gas diffusion layer is obtained by the same method as in Example 1. The results are: poor compatibility between gas diffusivity and conductivity, and low power generation performance. The results are shown in Table 2.

[0187] [Table 1]

[0188]

[0189] [Table 2-1]

[0190]

[0191] [Table 2-2]

[0192]

[0193] [Table 2-3]

[0194]

[0195] [Table 2-4]

[0196]

[0197] Description of Reference Numerals

[0198] 0, 0a, 0b: Gas diffusion layer

[0199] 1, 1a, 1b: Carbon sheet

[0200] 2: Surface X (microporous layer side)

[0201] 3: Surface Y (diaphragm side)

[0202] 4: Internal pores

[0203] 5, 5a, 5b: Microporous layer

[0204] 6, 6a, 6b: Catalyst layer

[0205] 7: Electrolyte membrane

[0206] 11: Thickness of carbon sheet

[0207] 12: The thickness of the inner pores

[0208] 13: Thickness of the microporous layer

[0209] 21: Mass flow controller

[0210] 22: Piping A

[0211] 23: Valve A

[0212] 24: Pressure controller

[0213] 25: Valve B

[0214] 26: Piping B

[0215] 27: Gas Chamber A

[0216] 28: Gas Diffusion Layer

[0217] 29: Gas Chamber B

[0218] 30: Pipe C

[0219] 31: Gas flow meter

[0220] 32: Sealing material

[0221] 33: Nitrogen

[0222] W: Width direction

[0223] D: Depth direction

Claims

1. A gas diffusion layer comprising a carbon sheet and a microporous layer on at least one side of the carbon sheet, When a region of the gas diffusion layer with a width of 10 mm and a depth of 3 mm selected arbitrarily from one side of the gas diffusion layer is compressed at a pressure of 0.5 MPa in a direction perpendicular to the surface, the "in-plane oxygen permeability coefficient" of oxygen permeating from the inside of the gas diffusion layer in the in-plane direction is set to A. The "resistance" when the gas diffusion layer is compressed in a direction perpendicular to the surface at 2 MPa is set to B. When the number obtained by subtracting 60 and multiplying B from A and adding 310 is set as the "compatibility index of in-plane oxygen permeability coefficient and electrical resistance" C, Satisfying the relationship that C is greater than 0, The carbon sheet has: a region including carbon fibers having voids having a pore diameter of 10 μm or more and 100 μm or less; and The area occupied by the internal pores with a pore diameter of 0.01 μm or more and less than 10 μm, The internal pores are included inside the surface side of the carbon sheet, and the internal pores exist with an average thickness of 10 μm or more and 30 μm or less in a direction perpendicular to the surface of the carbon sheet.

2. The gas diffusion layer according to claim 1, wherein: The unit area weight of the internal pores is 3 g / m 2 Above and 15g / m 2 the following.

3. The gas diffusion layer according to claim 1 or 2, wherein: The carbon sheet contains a fluorine-based water repellent and has a microporous layer only on one side, and on the opposite side, a ratio of the number of fluorine atoms to the number of carbon atoms on the surface carbon fibers is 0.002 or more and 0.030 or less.

4. The gas diffusion layer according to claim 1 or 2, wherein: The porosity of the internal pores is 80% or more and 95% or less.

5. The gas diffusion layer according to claim 1 or 2, wherein: When the range from the surface of the carbon sheet having the microporous layer to a position 20 μm in the perpendicular direction to the surface is defined as the surface layer, the density of the surface layer of the carbon sheet is 0.34 g / cm 3 The overall density of the carbon sheet is 0.29 g / cm 3 Above 0.33g / cm 3 the following. 6 . A membrane electrode assembly comprising the gas diffusion layer according to claim 1 .

7. A fuel cell comprising the membrane electrode assembly according to claim 6.